2000
DOI: 10.1021/jm000339w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ring Fluorination on the Pharmacology of Hallucinogenic Tryptamines

Abstract: A series of fluorinated analogues of the hallucinogenic tryptamines N,N-diethyltryptamine (DET), 4-hydroxy-N,N-dimethyltryptamine (4-OH-DMT, psilocin), and 5-methoxy-DMT was synthesized to investigate possible explanations for the inactivity of 6-fluoro-DET as a hallucinogen and to determine the effects of fluorination on the molecular recognition and activation of these compounds at serotonin receptor subtypes. The target compounds were evaluated using in vivo behavioral assays for hallucinogen-like and 5-HT(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 44 publications
4
98
0
Order By: Relevance
“…Several studies indicate that psilocin acts as an agonist at 5-HT 1A , 5-HT 2A , and 5-HT 2C receptors. 12,13,24) Furthermore, 5-HT 2A/2C receptors are expressed in the rodent prefrontal cortex. 28,29) The hallucinogenic 5-HT 2A/2C agonist 4-iodo-2,5-dimethoxyamphetamine indirectly increases extracellular 5-HT release in the rat medial prefrontal cortex by stimulating glutamate release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that psilocin acts as an agonist at 5-HT 1A , 5-HT 2A , and 5-HT 2C receptors. 12,13,24) Furthermore, 5-HT 2A/2C receptors are expressed in the rodent prefrontal cortex. 28,29) The hallucinogenic 5-HT 2A/2C agonist 4-iodo-2,5-dimethoxyamphetamine indirectly increases extracellular 5-HT release in the rat medial prefrontal cortex by stimulating glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…11) Recent pharmacological studies suggest that the hallucinogenic effects of psilocin and psilocybin are produced mainly because these compounds act as 5-HT receptor agonists that bind 5-HT 1A , 5-HT 2A , 5-HT 2B , and 5-HT 2C receptors with moderate to high affinity. 12,13) The effects of psilocybin are blocked by pretreatment with the 5-HT 2A antagonist ketanserin, indicating that the hallucinogenic effects of psilocybin are mediated primarily by 5-HT 2A stimulation. [14][15][16] Thus, 5-HT 2A receptor activation is necessary for the indoleamine hallucinogenic effects of psilocybin.…”
mentioning
confidence: 99%
“…In the study by Blair et al, 6 the effect of ring fluorination also was studied for four other tryptamines, where comparisons were made between 6-and 7-F-psilocin and 4-and 6-fluoro-5-methoxyDMT, 1, 2, 3, and 4, respectively ( Figure 3) with their nonfluorinated counterparts. Fluorination of psilocin in either the 6-or 7-position had identical effects on affinity at the rat 5-HT 2A receptor, reducing it by about one-half compared with psilocin itself.…”
Section: Ring Substituentsmentioning
confidence: 99%
“…Later suggestions focus on the 5-HT 1A receptor (Marona-Lewicka and Nichols 1995). In a particularly interesting study, Blair et al (2000) reported that ring fluorination of hallucinogenic tryptamines reduced the degree of mimicry of the stimulus effects of LSD by these drugs while at the same time diminishing their affinity for the 5-HT 1A receptor. The tryptamines, ranging from classic agents such as DMT (Sai-Halasz et al 1958) to a series of ring-and amine-substituted agents such as DPT (Fantegrossi et al 2008b;Li et al 2008), 2,5-dimethoxy-4-n-propylthiophenethylamine (Fantegrossi et al 2005), and 5-methoxy-N,N-diisopropyltryptamine (Fantegrossi et al 2006), are unquestionably hallucinogenic (Shulgin and Shulgin 1997) yet binding data regularly indicate that their highest affinity is for 5-HT 1A receptors.…”
Section: Neurochemical Bases Of Stimulus Control By Hallucinogensmentioning
confidence: 99%
“…Furthermore, Vollenweider et al (1996) observed that the subjective effects in normal subjects of psilocybin are blocked by ketanserin (Vollenweider et al 1996(Vollenweider et al , 1998a, an antagonist with low nanomolar affinity for 5-HT 2A receptors (Richelson and Souder 2000) and only micromolar affinity for 5-HT 1A receptors (Boess and Martin 1994). Receptor binding data provided no clue in that Blair et al (2000) observed K I values for psilocin of 49, 25, and 10 nM for 5-HT 1A , 5-HT 2A , and 5-HT 2C receptors, respectively. Nonetheless, given the close structural similarity of 5-MeO-DMT and both psilocybin and psilocin (Fig.…”
Section: Neurochemical Bases Of Stimulus Control By Hallucinogensmentioning
confidence: 99%